GERAKAN SOSIAL FORBALI DALAM MENGHENTIKAN REKLAMASI TELUK BENOA TAHUN 2014-2018 - Lestari, Tatik Dwi; Ali Azhar, Muhammad; Jayanthi Mertha, A.A. Sagung Mirah Mahaswari (Jurnal Nawala Politika; 2019, 2019)
ABSTRACT   Reclamation of Benoa Bay is a serious problem faced by the Balinese people. ForBALI has succeeded in becoming a large organization in which there are customs, artists, young people and environmental activists. The method used in this study is a qualitative descriptive research method. In this study the theory used is the Theory of New Social Movements and Resource Mobilization Theory. The successful mobilization of resources for the social movement carried out for years by ForBALI was finally able to stop the reclamation plan of Benoa Bay. The social movement carried out by ForBALI runs dynamically and is not standard as long as it fits the agreed strategy. ForBALI Strategy uses collective agreement and needs for the situation. A consistent movement for approximately four years and the role of the actors who are members of ForBALI are the key to the social movement carried out by ForBALI.   Keywords : Reclamation, New Social Movement, Resource Mobilization